Ride Analysis For Suspension System of off-Road Tracked Vehicles - Kasim, Salim Y. (Cranfield University, 1991)
In this work. an attempt has been made to develop a programming package for ride analysis of off-road vehicles based upon a finite-element formulation of vehicle suspension systems. Mathematical modelling of generalised suspension systems has been carried out with several non-linear aspects being investigated and implemented in the programming package. such as large deflection. non-linear characteristics of springs and dampers. bump stops and wheel separation. Different types of soi 1 have been considered together with an appropriate modelling of vehicle tracks. Several methods for time integration of dynamic equations have been investigated so as to deal wi th numerical instabi 1 i ty problems expected for off-road suspension systems which often have "stiff" differential equations of motion. Three ride analysis criteria have also been considered in the programming package. Several case studies have been analysed using the developed programming package. They consist of two simple case studies with known analytical solutions. an existing wheeled off-road vehicle with published analog computer resul t s , and an off-road tracked vehicle wi th known experimental results. The package has been validated and proved to be an acceptable tool for the ride analysis of off-road vehicles. within the approximating assumptions considered. Several measures for future development have also been suggested.